Differential development from cyanobacterias in native and agricultural soils in Córdoba province - Murialdo, R.; Fernández Belmonte, C.; Daga, C.; Gudiño, G. L.; Pesci, H.; González, C. M.; Reyna, E. (2024)
Fil: Murialdo, R. Universidad Nacional de Córdoba. Facultad de Ciencias Exactas, Físicas y Naturales; Argentina.